Bullying and Suicide Risk Among Pediatric Emergency Department Patients. Issue 6 (June 2016) - Stanley, Ian H.; Horowitz, Lisa M.; Bridge, Jeffrey A.; Wharff, Elizabeth A.; Pao, Maryland; Teach, Stephen J.
Abstract : Objectives: This study aimed to describe the association between recent bullying victimization and risk of suicide among pediatric emergency department (ED) patients. Methods: Patients presenting to 1 of 3 different urban pediatric EDs with either medical/surgical or psychiatric chief complaints completed structured interviews as part of a study to develop a suicide risk screening instrument, the Ask Suicide-Screening Questions. Seventeen candidate items and the criterion reference Suicidal Ideation Questionnaire were administered to patients ages 10 to 21 years. Bullying victimization was assessed by a single candidate item ("In the past few weeks, have you been bullied or picked on so much that you felt like you couldn't stand it anymore?"). Results: A total of 524 patients completed the interview (34.4% psychiatric chief complaints; 56.9% female; 50.4% white, non-Hispanic; mean [SD] age, 15.2 [2.6] years). Sixty patients (11.5%) reported recent bullying victimization, and of these, 33 (55.0%) screened positive for suicide risk on the Ask Suicide-Screening Questions or the previously validated Suicidal Ideation Questionnaire. After controlling for demographic and clinical variables, including a history of depression and drug use, the odds of screening positive for suicide risk were significantly greater in patients who reported recent bullying victimization (adjusted odds ratio, 3.19; 95% confidence interval, 1.66–6.11). After stratification by chief complaint, this association persisted for medical/surgical patients but not for psychiatric patients. Conclusions: Recent bullying victimization was associated with increased odds of screening positive for elevated suicide risk among pediatric ED patients presenting with medical/surgical complaints. Understanding this important correlate of suicide risk in pediatric ED patients may help inform ED-based suicide prevention interventions.